Landing : a textual garden - Etkin, Shelley (My University, 2019)
This text proposes various orientations towards a body of artistic research on the praxis of landing. Landing explores practices of mutual communicative exchange with land. The guiding curiosity in this practice is to shift from ‘land’ as a territorial entity, separate from the human, into ‘landing’ as a shared process. Thus far, landing has been practiced in the form of sessions, in private and group formations. Landing as a verb connotes processual movement and has been researched through embodied somatic journeying, practiced in several places, working with body and land as medium, proposing a morphing connectedness to address them as a whole. Landing offers a specific approach to journeying as a mode to potentially access a shared imaginary inclusive of humans and land. Through this, I ask how the practice might open into subtle aspects of colonization and de/territorialization and whether there lies potential for other modes of journeying. Landing as a praxis is discussed in relation to ecology, performance, healing, and pedagogy. This text seeks to enter into the research questions of landing as a multilogue; a whole composed of conversations, questions, and orientations. I have set the intention to experiment with attempts at deterritorializing practice through proposing a textual garden, in this case gardening through the medium of words, language, and text.
Keywords: land; landing; place; deterritorialization; somatic; journey; Intuition.; Imagination.; Communication.; Healing.; Transformation.; Colonization.; Reading.; Gardens.; Ecology.; Performance art.; intuitio; mielikuvitus; viestintä; parantaminen (paremmaksi muuttaminen); ekologia; puutarhat; performanssi; esitystaide; tekstuaalisuus; intuition; inbillningsförmåga; kommunikation; förbättring; ekologi; trädgårdar; performance; performativ konst; textualitet; MAECP